Tadeusz Kantor – projekt tekstoterapii kulturowej - Kapusta, Anna (2016)
The article reports the theoretical basis for use of the Tadeusz Kantor’s achievements in workshops’ activities as a resource for bibliotherapy (the therapeutic impact of a literary cultural texts) and cultural textotherapy (the sum of the actions and bibliotherapeutical support and activating the carnal and sensual perception of nonverbal cultural texts). The authoress proposes a new interpretations of Tadeusz Kantor’s works in the context of the problems dealt with in the individual personal development. According to Kantor’a idea of living museum, today the symbolic space for the cultural textotherapy can be the institution of museum hosting cultural texts. The museum is also – in this perspective – open to diverse therapeutic work, the center for personal development. In fact, cultural texts can support the social health and personal development, also anhanced by core values of cultural tradition.
Keywords: bodywork; museum; cultural textotherapy; Tadeusz Kantor; bibliotherapy